Integrating ICT competencies into high-order thinking skills assessment for preparing students’ mathematics learning autonomy in Indonesia - Ndiung, Sabina; Menggo, Sebastianus (International Journal of Innovative Research and Scientific Studies, 2025)
The objective of the current study was to determine the proficiency and challenges related to the development of ICT literacy skills and autonomy in mathematics learning for pupils attending secondary school in Indonesia. A survey was conducted with 560 students. The data was collected through interviews and questionnaires and analyzed using quantitative and qualitative methods. Respondents showed modest ICT proficiency, as indicated by the study. Twenty statements measured ICT literacy, whereas ten questions measured mathematics learning autonomy. Lack of enthusiasm and possession of digital media expertise, affordability for internet data assistance, lack of financial resources to use specific Mathematics-learning apps, unreliable internet access, and inadequate technology infrastructure at educational institutions hampered respondents’ ICT satisfaction. Numerous obstacles hinder those with disabilities from being ICT literate. Secondary schools in Indonesia are suggested to overcome these obstacles and use them to improve students’ mathematics skills and grades.